Study of Acute and Chronic Sinusitis – Symptoms, Diagnosis and Treatment: A Review article - Salman Jasim, Husam; Abed Saoud, Shaimaa; A. J. Almuslamawy, Haider (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Background: Sinusitis is an inflammatory condition that affects the mucous membrane lining the airways. Chronic rhinosinusitis and acute rhinosinusitis are the two types. Rhinosinusitis is characterized by facial pain, congestion, and headache. Due to the widespread prevalence of sinusitis, there must be an evaluation of the case because the diagnoses are more serious in the advanced stages of the disease and impact the outcome of care. Objectives: The objective of this study was to conduct a literature evaluation of chronic and acute rhinosinusitis, risk factors, symptoms and signs of sinusitis, diagnostic, sinusitis treatment, and antibiotic treatment, as well as new databases. Conclusion: Rhinosinusitis diagnosis is based on physician experience, with the history and examination serving as the foundation. It is just as vital to identify the underlying pathogen as it is to understand the patient's comorbidities to develop a proper treatment approach and minimize unwanted consequences.